1986
DOI: 10.1073/pnas.83.10.3361
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR2, -DR5, and DRw6 associated Dw subtypes correlate with HLA-DR beta and -DQ beta restriction fragment length polymorphisms.

Abstract: DNAs extracted from peripheral blood leukocytes of 24 individuals, selected for their HLA-DR types, -DR2, -DR5, and -DRw6, were analyzed with four restriction enzymes, BamHI, EcoRV, HindIll, and Taq (al, a2) and 2(3 ((31, /32). In addition DZa and DO/3 genes have been characterized but not yet located (2, 3). The numerous antigens encoded by these loci were initially characterized by alloantisera against DR and DQ, homozygous typing cells (HTC), and by primed lymphocytes for D and DP determinants.The specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…1). This DQ pattern has always been found in DRw16/DQwl Caucasoid healthy controls (7,22,23). Conversely, no T-cell clone reactivity was observed with DRw1S-positive IDDM APC ( Table 2), indicating that DR and DQ products from DRw15 and DRw16 haplotypes are not functionally related among type I diabetic patients, as previously demonstrated by us with healthy controls (18,19).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…1). This DQ pattern has always been found in DRw16/DQwl Caucasoid healthy controls (7,22,23). Conversely, no T-cell clone reactivity was observed with DRw1S-positive IDDM APC ( Table 2), indicating that DR and DQ products from DRw15 and DRw16 haplotypes are not functionally related among type I diabetic patients, as previously demonstrated by us with healthy controls (18,19).…”
supporting
confidence: 80%
“…Control healthy individuals refers to a series of nine DRw15/Dw2 or Dw12 or DRw16/Dw21 healthy Caucasoid donors. Each pattern associated with Dw2l, Dw2, and Dw12 (7,22,23) is shown in this figure.…”
mentioning
confidence: 99%
“…Genomic DNA from 89 sheep, digested with five restriction endonucleases (Barn HI, E m RI, Hin dIII, Pvu I1 and Taq I) and successively hybridized to ovine exon2 specific DQB and DRB probes detected 4 1 distinct and clear-cut fragments with the DQB probe (of which three were constant in all 89 animals) and 32 fragments with the DRB probe (of which 12 were constant). The intensity of a band on the autoradiogram allowed its assignment to a specific DQB or DRB fragment (Font et al 1986). For example, the DQB fragments were those detected only with the DQB probe, or those presenting a stronger signal with this probe.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on frequencies and associations of HLA-DR and HLA-D determinants in Caucasian and non-Caucasian populations have shown that serologically defined HLA-DR antigens can usually be subdivided by cellularly defined HLA-D determinants (Grosse-Wilde et al 1984, Layrisse et al 1978, Suciu-Foca et al 1981, Amar et al 1982, Duquesnoy et al 1984. In addition to the officially recognized cellular splits of the antigens HLA-DR2, DR4, DRw6 and DR7 (Sasazuki et al 1980, Batchelor et al 1984, Jaraquemada et al 1984, Honeyman et al 1984, more recent studies indicate that fur-* National Tissue Typing Laboratory (Council of Europe) National Blood Group Reference Laboratory (WHO) ther LD defined splits of HLA-DR specificities exist (Font et al 1986, Bach et al 1987, Bidwell et al 1986, Hajek-Rosenmayr et al 1986). Biochemical and moleculargenetic analysis of HLA-DR antigens and their HLA-D splits in general have confirmed these results, showing that polymorphisms of DR, of DR and DQ polypeptide chains and DQ polypeptide chains contribute to the generation of HLA-D haplotypes recognized by cellular reactions (David et al 1983, Nepom et al 1983, Nepom et al 1984, Haziot et al 1985, Baldwin et al 1985, Karr 1986, Bosch et al 1987.…”
mentioning
confidence: 84%